Frictions and Actions: The Actor's Role in Ethnodrama. (February 2019) - Vachon, Wolfgang; Hossain, Rahat; Ramsay, Natalie; Moore, Mo; Milo, Michael
Despite the growing body of literature in ethnotheater and ethnodrama, there has been little written about the role, responsibilities, and experiences of actors within the process. This article takes the reflections of one actor preparing, performing, and processing an ethnotheater production. Six "frictions" are identified and explored, leading to several recommendations for researchers, writers, actors, directors, and others involved in developing ethnodrama, ethnotheater, and ethnoperformances.